Factors Influencing Purchase Interest in LOCKNLOCK Products - Nazar, Muhammad; Siregar, Widyana Verawaty; Bachri, Naufal; Heriyana (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
This study analyzes the factors that affect the buying interest in LocknLock products, especially from the perspective of consumer value who care about the environment and attitudes towards products. This study uses a quantitative method with a purposive sampling technique. The sample consisted of 120 respondents who were consumers in Lhokseumawe City who had never bought or used environmentally friendly products. The sample was selected to represent potential consumers for eco-friendly products, such as LocknLock products. The findings showed that the variables of attitude on products had a positive and significant effect on buying interest, while the variables of altruism, innovation, environmentally friendly consumer values, and perception of communication behavior did not have a significant effect on bell interest. These results underscore the importance of increasing certain factors to increase buying interest. The study provides a new perspective with a focus on consumers in Lhokseumawe, which is different from previous research in Germany. In addition, this study shows that attitudes towards products have a more significant influence than other factors such as altruism, innovation, environmentally friendly consumer values, and perception of communication behaviors that were previously considered important in many studies. This research provides practical benefits for companies by helping them understand the importance of increasing consumers' positive attitudes towards eco-friendly products to encourage buying interest. This research also helps companies in designing more effective communication strategies to increase buying interest.